KURIKULUM PENDIDIKAN BERBASIS TAUHID: Landasan Filosofis dan Manajemen Kurikulum SMP ar-Rohmah Putri Boarding School Malang - Umiarso, Umiarso; Mawardianti, Indri (Muaddib : Studi Kependidikan dan Keislaman, 2018)
Tauhid is the main core and the main foundation of Islamic teachings that need to be reflected in the world of education. Therefore, monotheism-based education into all activities includes coaching, fostering and developing students' self-potential that comes from God. So this research is focused on the discussion of the construction of a monotheism-based education curriculum applied by Ar-Rohmah Putri Middle School Malang Boarding School along with its management (management). This research uses a qualitative approach that is a type of case study with in-depth interviews and participant observation as data collection techniques. While analyzing data, researchers used the interactive models of Miles and Hubermann. This research concludes, curriculum construction in the institution refers to the systematic revelation as the basis of tauhid-based education. The foundation is seen from the typology of the philosophy of Islamic education including the category of Tawhid-based Social Reconstruction. Curriculum management includes the planning process by formulating a mission and goal vision; organizing is focused on the integration of religion and science; its application includes the values of monotheism and the views of Islam into subjects; and evaluating using adab evaluation.